A retrospective study to evaluate antibiotic prescribing for pediatric appendectomy procedures - Abid, Mohammed Ashraf (Curtin University, 2006)
Objective: To retrospectively evaluate antibiotic use in pediatric appendectomy procedures following an educational intervention in December 2001. Methodology: Demographic, clinical, and prescribing data was collected for all the patients <18 years old who have had undergone non-perforated appendectomy procedures at Princess Margaret Hospital for Children, WA. Data collection and analysis were divided into three groups. Group-I involved patients from May 2002 to April 2004 (which followed the post-intervention follow-up conducted from December 2001-April 2002 by Mallik et al.1). In May 2004, the Western Australian Therapeutic Advisory Group (WATAG) sent an advisory note which recommended a change from the use of cefotetan for surgical prophylaxis to cephazolin plus metronidazole. Group-II of the study involved patients between May 2004 (when the WATAG note was released) and June 2004; while Group-III involved patients from July 2004 to April 2005 (when the hospital issued the new guidelines and withdrawn cefotetan).Patient records were randomly selected for Group I & III and all the records were evaluated for Group III. Results: Records for 408 patients were evaluated across the three groups of the study. There no significant difference (p>0.05) between gender and age across the three groups. An appropriate prophylactic drug regimen was prescribed in 68.5%, 66.7% and 39.8% of patients in Groups I, II and III respectively, with a significant difference in appropriate drug choice between Groups I and III (p <0.05). There was no significant difference between the groups with respect to appropriate prophylactic drug dose (p>0.05). Appropriateness rates for antibiotic choices for ward treatment were high at 91.0%, 92.0% and 92.7%, with no significant differences (p>0.05).There was a significant difference (p<0.05) between the three groups regarding the number of doses for ward treatment, with inappropriateness rates of 29.9%, 40% and 16.4%. The total appropriateness rates (drug choice plus dose in theatre and ward) across the study were 54.7%, 54.2% and 31.5%, with a significant difference (p <0.05) between Groups I and III. Conclusion: This study has identified deficiencies related to the prescribing of antibiotics for prophylaxis. There was a varied level of prescribing appropriateness in terms of antibiotic choice for prophylaxis with an increasing trend for inappropriateness towards the end of the study period. This would indicate that issuing of changed guidelines and withdrawal of the drug being replaced did not positively influence appropriate prescribing. Further interventions are required to improve compliance with hospital prescribing guidelines.